Origin of Two-Dimensional Vertical Ferroelectricity in WTe2 Bilayer and Multilayer - Yang, Qing; Wu, Menghao; Li, Ju (The journal of physical chemistry letters, 2018)
In a recent report, room-temperature vertical ferroelectricity was experimentally shown in WTe2 bilayer, while its mechanism of ferroelectric switching without vertical ion displacements remains unclarified. In this work, we reveal its origin by first-principles calculations that the polarization stems from uncompensated interlayer vertical charge transfer depending on in-plane translation, which can be switched upon interlayer sliding. The calculated results are consistent with experimental data, and a similar switching mechanism can be applied to a multilayer counterpart. Despite its small ferroelectric switching barrier and polarization, the in-plane rigidity of WTe2 layer gives rise to a high Curie temperature. A moire pattern of ferroelectric domain superlattice can be formed and tuned upon a small-angle twist of bilayer, which is unique compared with traditional ferroelectrics. Similar interlayer translational ferroelectricity may exist in a series of van der Waals bilayers or even bulk phases.